Voluntary matching grants can forestall social dumping - Jacques H. Drèze; Charles Figuières; Jean Hindriks (Center for Economic Studies and ifo Institute (CESifo), 2006)
The European economic integration leads to increasing mobility of factors, thereby threatening the stability of social transfer programs. This paper investigates the possibility to achieve by means of voluntary matching grants both the optimal allocation of factors and the optimal level of redistribution in the presence of factor mobility. We use a fiscal competition model a la Wildasin (1991) in which states differ in their technologies and preferences for redistribution. We first investigate a simple process in which the regulatory authority progressively raises the matching grants to the district choosing the lowest transfer and all districts respond optimally to the resulting change in transfers all around. This process is shown to increase total production and the level of redistribution. However it does not guarantee that all districts gain, nor that an efficient level of redistribution is attained. Assuming complete information among districts, we first derive the willingness of each district to match the contribution of other districts and we show that the aggregate willingness to pay for matching rates converges to zero when both the efficient level of redistribution and the efficient allocation of factors are achieved. We then describe the adjustment process for the matching rates that will lead districts to the efficient outcome and guarantee that everyone will gain.
Keywords: H23; H70; 330; Finanzföderalismus; Finanzausgleich; Öffentlicher Transfer; Verteilungswirkung; Theorie